"Caracterización físico-química y sensorial del aceite extraído de las semillas de jaca (Artocarpus heterophyllus), mediante métodos de prensado en frio y caliente” - León Díaz, Jean Carlos (2025)
This research aimed to characterize the physicochemical and sensory properties of oil extracted from jackfruit (Artocarpus heterophyllus) seeds using cold and hot pressing methods. Jackfruit, a tropical fruit that remains underutilized in many countries, has seeds with high oil content and potential as a vegetable oil source. The study evaluated how different extraction temperatures affect the oil’s yield, density, acidity index, color, and odor. Cold pressing was carried out at 30, 35, and 40 °C, and hot pressing at 80, 90, and 100 °C, each with three repetitions. The results revealed significant variations between both methods, with temperature increases clearly influencing the analyzed properties. The extracted oil showed characteristics that position it as a potential product of interest for the food and cosmetic industries, particularly due to its pleasant color and aroma, as well as its acceptable yield under optimal conditions. This study contributes to the integral use of jackfruit by promoting its added value and exploring its industrial applications. It also emphasizes the importance of selecting appropriate extraction conditions to preserve the quality of the obtained oil.